VDAC closure increases calcium ion flux - Tan, Wenzhi (2007)
VDAC is the major permeability pathway in the mitochondrial outer membrane and can control the flow of metabolites and ions. Therefore Ca(2+) flux across the outer membrane occurs mainly through VDAC. Since both Ca(2+) fluxes and VDAC are involved in apoptosis, we examined whether Ca(2+) is required for channel formation by VDAC isolated from rat liver. The voltage gating of VDAC does not require Ca(2+) and it functions normally with or without Ca(2+). Additionally, VDAC generally shows a higher permeability to Ca(2+) in the closed states (states with lower permeability to metabolites) than that in the open state. Thus VDAC closure, which induces cell death, also favors Ca(2+) flux into mitochondria, which can also lead to permeability transition and cell death. These results are consistent with the view that VDAC closure is a pro-apoptotic signal.